Kelembagaan Pelayanan Kartu Identitas Anak di Kabupaten Buton Tengah - Zainul Abidin (Jurnal Administrasi Publik, 2022)
This research is a qualitative research which intends to describe the institution of child identity card services in Central Buton Regency. The approach used is descriptive. Data collection was obtained through observation, interviews and documents. Analysis of the data used is an interactive model. This study found that the child identity card service institution in Central Buton Regency was running and in good condition. Bureaucratic structure, job description and service system synergize and have a positive impact on service effectiveness. However, there are obstacles related to the convenience of obtaining services and the location of the office which is still far from the community outside the capital of Central Buton Regency, Labungkari for offline or direct services. The pursuit of target coverage for child identity card services has been hampered due to the COVID-19 pandemic and has disrupted the disposition of existing bureaucrats